2016
DOI: 10.1111/irv.12354
|View full text |Cite
|
Sign up to set email alerts
|

Influenza hospitalization epidemiology from a severe acute respiratory infection surveillance system in Jordan, January 2008–February 2014

Abstract: BackgroundAcute respiratory infections (ARIs) are a major cause of morbidity and mortality worldwide. Influenza typically contributes substantially to the burden of ARI, but only limited data are available on influenza activity and seasonality in Jordan.MethodsSyndromic case definitions were used to identify individuals with severe acute respiratory infections (SARI) admitted to four sentinel hospitals in Jordan. Demographic and clinical data were collected. Nasopharyngeal and oropharyngeal swabs were tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 7 publications
5
32
1
Order By: Relevance
“…Therefore, children have SARI were more likely to be involved in the surveillance. Similar results have been obtained in Mongolia [10], Philippines [11], Jordan [23]. Our findings further demonstrated that young children are vulnerable for both mild and severe respiratory infection, and the low influenza detection rate among 0–4 years age-group in both SARI and ILI patients foreshadow the need of expand the respiratory illness surveillance to more types of pathogens [12,24].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, children have SARI were more likely to be involved in the surveillance. Similar results have been obtained in Mongolia [10], Philippines [11], Jordan [23]. Our findings further demonstrated that young children are vulnerable for both mild and severe respiratory infection, and the low influenza detection rate among 0–4 years age-group in both SARI and ILI patients foreshadow the need of expand the respiratory illness surveillance to more types of pathogens [12,24].…”
Section: Discussionsupporting
confidence: 88%
“…This positivity rate is much lower than that reported from neighbouring and Asian countries like Pakistan (24%), China (30%), Bangladesh (10%), and Jordan (9%) (14)(15)(16)(17), which have similar sentinel surveillance systems, and may suggest some underestimation. Nonetheless, it should be noted that after more than 3 decades of war and conflict, the system was able to detect and respond successfully to the novel influenza virus circulating during the influenza A (H1N1) pandemic in 2009.…”
Section: Discussioncontrasting
confidence: 68%
“…Although the influenza positivity among SARI cases was reported to be 8% in Oman, (4) and 9% in Jordan (18), both in the Eastern Mediterranean Region of WHO, the influenza positivity among SARI cases in Asia and Africa found in other studies (5,9,17,(19)(20)(21) ranged between 8-11%. The reasons why we found a higher percentage of influenza positivity amongst SARI cases could be attributed to the fact that we sampled 93% of all SARI cases that met the WHO case definition for SARI while in all those countries where a low (18). However, owing to the fact that we collected data for only one year and from only one district in Egypt, this information may not suffice to determine influenza seasonality in the country.…”
Section: Influenza Incidencementioning
confidence: 85%